2019
DOI: 10.1021/acsami.9b00090
|View full text |Cite
|
Sign up to set email alerts
|

Membranes with Functionalized Nanopores for Aromaticity-Based Separation of Small Molecules

Abstract: Membranes that can separate molecules of similar size based on chemical features could transform chemical manufacturing. We demonstrate membranes with functional, 1–3 nm pores prepared using a simple and scalable approach: coating a porous support with random copolymer micelles in alcohol, followed by precipitation in water and functionalization of pore surfaces. This approach was used to prepare membranes that can separate two hormones of similar size and charge, differentiated by aromaticity, mediated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…This enhanced mixed-salt selectivity was due to the lower retention of Cl − during mixed-salt filtration (SI Appendix, Table S6). While the underlying mechanism is not yet clear, it is consistent with previous studies of membranes with nanoscale, functionalized pores (9,18). These results motivate further study of the synergistic use of nanoconfinement and chemical interactions to achieve previously inaccessible membrane separations (6).…”
Section: -supporting
confidence: 85%
See 1 more Smart Citation
“…This enhanced mixed-salt selectivity was due to the lower retention of Cl − during mixed-salt filtration (SI Appendix, Table S6). While the underlying mechanism is not yet clear, it is consistent with previous studies of membranes with nanoscale, functionalized pores (9,18). These results motivate further study of the synergistic use of nanoconfinement and chemical interactions to achieve previously inaccessible membrane separations (6).…”
Section: -supporting
confidence: 85%
“…However, the relatively large size of BCP membrane pores (>2 to 3 nm) limits its use for ion separations. Membranes formed from packed arrays of random copolymer micelles have demonstrated selectivity based on solute charge (9) and aromaticity (18), but the pore size of these membranes is also too large to separate salt ions. It has been shown that the transport properties of ion exchange membranes are affected by the compatibility between the ions and fixed charge groups (19,20), but this approach has not been utilized to design advanced membrane filters.…”
mentioning
confidence: 99%
“…The rudimentary NPC-like affinity-based selectivity is also observed in completely synthetic nanopores that use synthetic polymers [25], and provide a link to a wider field of design of polymer functionalized nanochannels for various nanotechnology applications such as protein sorting, DNA sequencing and ''smart'' materials [146,[188][189][190][191][192][193][194][195][196][197][198][199]. Such artificial nanopores, although not the direct focus of this review, can also serve as experimental venues for testing the conceptual models of NPC transport.…”
Section: Fg Nups In Npc Mimicking Synthetic Nanoporesmentioning
confidence: 99%
“…Yet these are efficiently filtered out, without clogging the NPC. In the more general context, the question of specificity and throughput in the presence of non-specific competition is important for the design of artificial nano-channels and biosensors that are capable of molecular sorting and detection under realistic conditions without fouling [193,301,302].…”
Section: Transport Protein Crowding Inside the Channelmentioning
confidence: 99%
“…In recently years, nanotechnology has gradually been applied in the agriculture and forestry pest control [ 9 , 10 ]. Especially, nanotechnology shows excellent properties in the transportation of agrochemicals, including fertilizers [ 11 ], pesticides [ 12 ] and hormones [ 13 ]. In 2019, International Union of Pure and Applied Chemistry (IUPAC) ranked nano-pesticides as the top ten emerging chemical technologies that could change the world [ 14 ].…”
Section: Introductionmentioning
confidence: 99%